ANALISIS KAUSALITAS ANTARA PENYALURAN KREDIT DENGAN PERTUMBUHAN EKONOMI (Studi Kasus Pada BPD Provinsi Nusa Tenggara Barat) - Apriana, Riska (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to determine the relationship that exists between lending Regional Development Bank of West Nusa Tenggara comprising : consumptive loans, working capital loans, and investment loans to the economy growth and see the effect of short-term and long-term. This type of research is descriptive quantitative, using granger causality test and Error Correction Model-ECM method over the periode 2008: Q1 – 2015: Q3. The results showed that between consumptive credit and economy growth has to two-way relationship in the short-term and long-term. And a one-way between investment loans and working capital loans.Keyword: consumptive loans, investment loans, working capital loans, economy growth